Improvement of grain processing via ultrasonic treatment - Rudik, F. Y.; Morgunova, N. L.; Semilet, N. A.; Tuliyeva, M. S. (IOP Conference Series: Earth and Environmental Science: Russian Conference on Innovations in Agricultural and Rural Development 2019, 2019)
The theoretical study made it possible to define the main correlation dependences affecting the efficiency of grain preparation for milling. Experimental studies allowed improving the technology of grain softening and washing. Design and operating parameters of ultrasonic facility and technology ensuring high degree of grain cleaning and moistening were studied and structured, namely: ultrasound frequency - 18 kHz; process temperature - 30-40 °C; processing time - 30-40 s; intensity of ultrasonic waves - 1 W/cm2 Теоретическое исследование позволило определить основные корреляционные зависимости, влияющие на эффективность подготовки зерна к помолу. Экспериментальные исследования позволили усовершенствовать технологию умягчения и промывки зерна. Исследованы и структурированы конструктивные и рабочие параметры ультразвуковой установки и технологии, обеспечивающие высокую степень очистки и увлажнения зерна, а именно: частота ультразвука - 18 кГц; температура процесса - 30-40 ° С; время обработки - 30-40 с; интенсивность ультразвуковых волн - 1 Вт / см2
Keywords: импакт-фактор 2019; зарубежное издание; скопус конференции; зарубежные авторы; помол зерна; тенхнология промывки зерна; процентиль 16; q4